2016
DOI: 10.5430/rwe.v7n1p80
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Stock Prices and Exchange Rate in Emerging Market Economies

Abstract: In this study we apply a series of non-causality tests to determine the direction of the relationship between stock price indices and exchange rates in emerging market economies. The data set includes monthly observations for the 21 countries included in the MSCI Emerging Markets Index between January 2003 and June 2013. The results indicate that there is a statistically significant causal interaction between the two variables in 13 of the 21 countries we study. The direction of the causality varies from count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The above findings will contribute to the existing literature by approving the view points of Frankel and Rodriguez (1975), Adjasi et al (2008), Agrawal, Srivastav and Srivastava (2010), Ahmad (2012), Hajilee and Nasser (2014), Frederick and Ijirshar (2015), Ngan (2016), Yaday (2016), Akdogu and Birkan (2016), Najaf and Najaf (2016) and Sichoongwe (2016). The above studies certify the wellestablished relation between FX rates and stock market.…”
Section: Garch (11) Modelsupporting
confidence: 64%
See 1 more Smart Citation
“…The above findings will contribute to the existing literature by approving the view points of Frankel and Rodriguez (1975), Adjasi et al (2008), Agrawal, Srivastav and Srivastava (2010), Ahmad (2012), Hajilee and Nasser (2014), Frederick and Ijirshar (2015), Ngan (2016), Yaday (2016), Akdogu and Birkan (2016), Najaf and Najaf (2016) and Sichoongwe (2016). The above studies certify the wellestablished relation between FX rates and stock market.…”
Section: Garch (11) Modelsupporting
confidence: 64%
“…Sichoongwe (2016) also found that there is a negative relationship between exchange rate volatility and stock market returns in Zambia. This relation was further confirmed by another study conducted in 21 emerging market economies (Akdogu & Birkan, 2016). Rafiq and Hasan (2016) confirmed a short-run relationship between exchange rate and stock prices by examining the context of Pakistan economy.…”
Section: Review Of Literaturesupporting
confidence: 62%
“…As a result of both the Angle-Granger and Johansen method being used, a link between the two variables could not be detected in the long term, which is valid for all four countries. Akdogu & Birkan(2016) conducted causality tests to determine the direction of the relationship between stock index and exchange rates in 21 developing country markets during the period covering the years 2003-2013. A statistically significant causality relation was found in 13 out of 21 countries as a result of the analysis done with the monthly selected data set.…”
Section: Literature Surveymentioning
confidence: 99%
“…As stock prices and foreign exchange rates act as barometers of the financial system and the state of the economy (Akdogu & Birkan, 2016). If the causal relationship between this two above mentioned variables can be established and the sequence of financial market phenomena behind instability can be recognized, it could help policy makers to avoid large scale financial instability and enhance the contribution of the financial markets to sustainable growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…There is extant literature on the relationship between stock prices and exchange rates in both developed and emerging economies but the results have been diverse and inconclusive as regards which of the models is most applicable to, or predominant within an economy (Richard et al 2009). Some group of studies (Adaramola, 2012;Akdogu & Birkan, 2016;Bala & Hassan, 2018) establishes that it is the exchange rate that causes the movements in stock prices, thereby supporting the flow oriented model. On the other hand, studies by Aydemir and Demirhan (2009), Richards, Simpson and Evans (2009), Kutty (2010), Umer, Sevil and Kamisli (2015), and Huy (2016) provide empirical evidence that causation runs from the stock price to exchange rate which implies the support of the stock oriented model.…”
Section: Introductionmentioning
confidence: 99%